Transcriptional Landscapes of Divergent Sporophyte Development in Two Mosses, Physcomitrium (Physcomitrella) patens and Funaria hygrometrica - Kirbis, Alexander; Waller, Manuel; Ricca, Mariana; Bont, Zoe; Neubauer, Anna; Goffinet, Bernard; Szövényi, Péter (Frontiers in Plant Science, 2020)
Understanding the molecular basis of morphological shifts is a fundamental question of evolutionary biology. New morphologies may arise through the birth/death of genes (gene gain/loss) or by reutilizing existing gene sets. Yet, the relative contribution of these two processes to radical morphological shifts is still poorly understood. Here we use the model system of two mosses, Funaria hygrometrica and Physcomitrium (Physcomitrella) patens, to investigate the molecular mechanisms underlying contrasting sporophyte architectures. We used comparative analysis of time-series expression data for four stages of sporophyte development in both species to address this question in detail. We found that large-scale differences in sporophytic architecture are mainly governed by orthologous (i.e., shared) genes frequently experiencing temporal gene expression shifts between the two species. While the absolute number of species-specific genes expressed during sporophyte development is somewhat smaller, we observed a significant increase of their proportion in preferentially sporophyte expressed genes, suggesting a fundamental role in the sporophyte phase. However, further functional studies are necessary to determine their contribution to diverging sporophyte morphologies. Our results add to the growing set of studies suggesting that radical changes in morphology may rely on the heterochronic expression of conserved regulators.